(untitled) (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2025)
Purpose: This study aims to provide a 360° strategic exploration of the Aditya Birla Group (ABG), a global conglomerate with operations in over 36 countries and leadership in sectors such as metals, cement, textiles, telecommunications, fashion retail, and financial services. By analyzing ABG’s adaptive strategies, sustainable growth initiatives, and innovation-driven culture, the research seeks to uncover how a diversified business group sustains resilience, competitiveness, and stakeholder trust in rapidly evolving global markets. Methodology: An exploratory case study approach was adopted, integrating qualitative and quantitative analyses. Strategic evaluation frameworks such as SWOC (Strengths, Weaknesses, Opportunities, Challenges) and ABCD (Advantages, Benefits, Constraints, Disadvantages) were applied alongside financial performance reviews, market trend analysis, and governance assessment. Data was sourced from open-access journals, annual reports, industry databases, and credible business news platforms. Results & Analysis: Findings highlight ABG’s sustained revenue growth, robust capital efficiency, and effective risk diversification across multiple verticals. The group’s technology-led retail transformation, expansion of lifestyle brands via TMRW, and ESG-driven business models have reinforced its market leadership. Analysis also reveals how ABG’s human resource strategies—anchored in leadership development, inclusivity, and analytics-driven decision-making—strengthen its talent pipeline across geographies. Identified challenges include aligning digital transformation with workforce adaptability, managing global diversity, and maintaining market agility in emerging economies. Originality / Value: This research contributes a nuanced understanding of how large diversified conglomerates can maintain competitive advantage through an integrated focus on sustainability, innovation, and cross-sectoral synergy. By presenting a rare deep-dive into ABG’s strategic architecture, it offers practical insights for policymakers, corporate strategists, and business educators seeking models of long-term growth in volatile environments. Type of Paper: Exploratory Case Study